2022
DOI: 10.1155/2022/8016474
|View full text |Cite|
|
Sign up to set email alerts
|

The Design of a Dual Servo Drive and Control Integrated Platform Based on VNet Neural Network

Abstract: A dual-servo drive and control integrated platform based on VNet neural network development is aimed to address the concerns of poor realization function, operational stability, and lengthy reaction time in the presently built dual-servo drive and control integrated platform. The VNet neural network model structure is established, the VNet neural network model is trained, and the VNet neural network adaptive control method is introduced. Based on VNet neural network development, the hardware design of the dual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…Security and Communication Networks has retracted the article titled "Te Design of a Dual Servo Drive and Control Integrated Platform Based on VNet Neural Network" [1] due to concerns that the peer review process has been compromised. Following an investigation conducted by the Hindawi Research Integrity team [2], signifcant concerns were identifed with the peer reviewers assigned to this article; the investigation has concluded that the peer review process was compromised.…”
mentioning
confidence: 99%
“…Security and Communication Networks has retracted the article titled "Te Design of a Dual Servo Drive and Control Integrated Platform Based on VNet Neural Network" [1] due to concerns that the peer review process has been compromised. Following an investigation conducted by the Hindawi Research Integrity team [2], signifcant concerns were identifed with the peer reviewers assigned to this article; the investigation has concluded that the peer review process was compromised.…”
mentioning
confidence: 99%